Effect of demographic disparities on the use of the JMP ladders for water, sanitation, and hygiene services in Bishoftu Town, Ethiopia - Aderajew Mekonnen Girmay; Zinabu Assefa Alemu; Sisay Derso Mengesha; Daniel Abera Dinssa; Bedasa Wagari; Mesaye Getachew Weldegebriel; Melaku Gizaw Serte; Tsigereda Assefa Alemayehu; Moa Abate Kenea; Abel Weldetinsae; Kirubel Tesfaye Teklu; Ermias Alemayehu Adugna; et al. (Discover Water, 2022)
Abstract Reducing inequalities in all its forms is one of the key principles of the Sustainable Development Goal (SDG). However, the 2030 SDG Agenda has been a real challenge in addressing inequalities in Water, Sanitation, and Hygiene (WASH) services. There is a disparity in the use of WASH services in Ethiopia. Therefore, this study aimed to identify demographic factors affecting the use of Joint Monitoring Program (JMP) ladders for WASH services. In this study, a total of 5350 households were included. Households having heads with vocational education levels were 2.9 times higher in use of basic drinking-water services ((Adjusted Odds Ratio (AOR) = 2.9 with 95% CI 1.6–5.1) than household having heads who could not read and write. Besides, households living in urban areas were 21.7 times more likely to use basic drinking-water services (AOR = 21.7 with 95% CI 16–30) than in rural parts. Further, households with merchants’ heads were 2.1 times higher to use basic sanitation services (AOR = 2.1 with 95% CI 1.5, 3.1) than households with farmers’ heads. Moreover, households having higher monthly income per head were 2.9 times higher in utilizing basic sanitation services (AOR = 2.9 with 95% CI 2.32–3.58) than the poorest households. Similarly, households with female heads were 1.5 times higher in using the JMP ladder for basic hygiene services (AOR = 1.5 with 95% CI 1.24–1.71) than households with male heads. Additionally, respondents who live in urban areas had 2.8 times higher use of basic hygiene services (AOR = 2.8 with 95% CI 2.26–3.54) than those in rural areas. Many demographic factors that influence the use of the JMP ladders for water, sanitation, and hygiene services were identified. The use of surface water, open defecation practice, unimproved sanitation, and no hygiene services were positively associated with illiteracy. The findings suggest that state authorities should initiate firm WASH policies and strategies to achieve the SDG 6 and 10. Additionally, the government should apply effective WASH interventions that consider demographic disparities.